Feeding preference of Phytoseiulus persimilis Athias-Henriot (Acari: Phytosei-idae) towards untreated and Beauveria bassiana-treated Tetranychus urticae (Acari: Tetranychidae) on cucumber leaves - Marjan Seiedy (Persian Journal of Acarology)
Determination of the host preference of predatory mites when receiving signals related to either untreated and Beauveria bassiana-treated Tetranychus urticae (Acari: Tetranychidae) is important in predicting the predatory mite’s reaction when encountering pathogens due to their coincident presence in greenhouses and fields. Here, we have studied the preference of female predatory mite, Phytoseiulus persimilis Athias-Henriot (Acari: Phytoseiidae) when choosing between untreated and B. bassiana-treated T. urticae (72 hours after treatment of spider mite by fungus) on leaves. This investigation showed a highly significant preference of P. persimilis towards untreated T. urticae (P< 0.0001). We concluded that the predatory mite is capable to recognize fungus-treated prey and prefers to prey on the uninfected ones. This suggests that the predatory mite and the fungus may be compatible agents of biological control.